THE INFLUENCE JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE TURNOVER INTENTION - Muhamad Ekhsan (Kusuma Negara Business School, 2019)
Human resources are one of the main assets in an organization, which can make an invaluable contribution to the organization's achievement strategy. The high level of turnover intention is a serious problem at PT Nippo Mechatronics Indonesia. This study aims to analyze how much influence job satisfaction and organizational commitment on turnover intention both partially and simultaneously. Determination of the sample is done by using probability sampling with a simple random sampling method. This research is quantitative research using double linear regression analysis as data processing. In this study, job satisfaction has a negative and significant effect on turnover intention. Organizational commitment negatively affects turnover intention. Job satisfaction and organizational commitment simultaneously have a significant effect on turnover intention.